Perceptions of geometry and cultural values on traditional woven fabric motifs of the Sasak people - Lalu Muhammad Fauzi; Nila Hayati; Rody Satriawan; Fahrurrozi Fahrurrozi (Universitas Hamzanwadi, 2023)
This cultural diversity can be utilized in exploring mathematical concepts bridged by ethnomathematics to bring mathematics closer to students' cultures. However, on the other hand, many people think that mathematics is culture-free. The uniqueness and diversity of cultures in ideas, activities, and artifacts can be studied and used as learning resources, especially in mathematics. Therefore, this study seeks to explore the geometrical perceptions and cultural values contained in the traditional woven fabric motifs of the Sasak people. This research is qualitative research with an ethnographic method. Research data were collected through observation, literature study, and interviews with cultural practitioners, traditional leaders, woven fabric craftsmen, and cultural. The results of this study indicate that the traditional woven fabrics of the Sasak people have recognized and used mathematical concepts, especially lines, angles, flat shapes, and geometric transformations, in the design of traditional woven fabric motifs of the Sasak people. In addition, there is a philosophical meaning contained in each motif or pattern. The meaning is in the form of cultural values such as moral, historical, and philosophical values, which are used as messages to their children and grandchildren.